2016
DOI: 10.1007/s00264-016-3113-7
|View full text |Cite
|
Sign up to set email alerts
|

The foot function index is more sensitive to change than the Leeds Foot Impact Scale for evaluating rheumatoid arthritis patients after forefoot or hindfoot reconstruction

Abstract: The FFI showed a large responsiveness and the LFIS- RA showed moderate responsiveness in rheumatoid arthritis patients receiving forefoot or hindfoot surgery, without floor or ceiling effects in both questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
5
2
1
Order By: Relevance
“…When evaluating patients with rheumatoid arthritis, this ceiling effect cannot be reproduced. 16 On the other hand, a floor effect was not documented in our cohort.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…When evaluating patients with rheumatoid arthritis, this ceiling effect cannot be reproduced. 16 On the other hand, a floor effect was not documented in our cohort.…”
Section: Discussioncontrasting
confidence: 57%
“…When evaluating patients with rheumatoid arthritis, this ceiling effect cannot be reproduced. 16 On the other hand, a floor effect was not documented in our cohort. Marked differences were seen between males and females, with lower (ie, better) mean values for males in all FFI scores and age groups.…”
Section: Discussioncontrasting
confidence: 57%
“…En la mayoría de los estudios sobre el FFI se habla de la gran utilidad de este instrumento en múltiples patologías dolorosas del pie, como reflejan Budiman-Mak y cols. que, en 2013, consideraron este cuestionario como pionero en la medición de la salud del pie, válido, reproducible y con una sensibilidad muy alta en distintas patologías limitantes del pie 20 . El FFI ha sido comparado incluso con el propio MFPDI por van der Zwaard y cols.…”
Section: Discussionunclassified
“…No floor or ceiling effects were observed for the LFIS‐RA in a study of 30 people with rheumatoid arthritis .…”
Section: Leeds Foot Impact Scale For Rheumatoid Arthritismentioning
confidence: 92%
“…A study of 30 patients with rheumatoid arthritis undergoing foot surgery found that the LFIS‐RA was less responsive than the FFI . Over a mean follow‐up of 38 months, the within‐group standard effect size for the LFIS‐RA was 0.58, the SRM was 0.58, and Guyatt Index was 0.90, indicating moderate internal responsiveness.…”
Section: Leeds Foot Impact Scale For Rheumatoid Arthritismentioning
confidence: 99%